Structure and function of phytonic Bacillus thuringiensis of wild rice genotype Oryza brachyantha A. Chev. and Roehr. - Acharya, Sonali; Padhi, Sanhita; Bose, L K; Dangar, T K (ORYZA-An International Journal of Rice, 2018)
Endospheric microbiome of unexplored wild rice, Oryza brachyantha (OB), was studied. Endogenous heterotrophic, spore forming, spore-crystal forming, nitrifying, denitrifying, P solubilizing bacteria, actinomycetes, and fungi in leaves, stems and roots were (0.07-4.48, 0.06-4.08, 5.00-4.00, 0.56-1.40, 0.06-0.40, 0.07, 0.03 and 0.14-8.00) x10 2 cfu/g, respectively and endo-colonizers were 5-6 times more in roots than other plant parts. Phenotypic characters, cry+/cyt+ in 6 SCF and 16S rDNA phylogeny of 2 potent SCF ascertained their identity as Bacillus thuringiensis (Bt). For the first time, 6 polyvalent Bt with biocidal and plant growth promotion (PGP) functions were identified from the wild rice OB. All endo-Bt possessed diverse anti-lepidopterancry genes which predicted their virulence against rice leaf folder (LF), Cnaphalocrocis medinalis Guenee. Only cry2 or cyt primers amplified expected sized amplicons from Bt 18, 20 and 21. Bt18 and Bt21 killed 60% LFlarvae in vitro by 2.65x104 and 7.56x104 cfu/ml and the former one was more virulent. They produced siderophore, amylase, protease etc. which would induce natural tolerance of OB against bacterial and fungal pathogens. Besides, the Bt had other PGP traits too viz., nitrate reduction, ammonia production, P solubilization etc. Therefore, the endo-microbiome of OB would modulate endospheric functionalities, promote growth and development, and impart natural endurance to OB against pests and diseases.